The validation of the malay translated sleep apnea quality of life index (saqli) in patients with obstructive sleep apnea - Mohd Yusof, Nor Idayu (2011)
Introduction: The Sleep Apnea Quality of Life Index (SAQLI) is a disease specific instrument developed to record the key elements of obstructive sleep apnea syndrome disorder that are important to patients and act as an outcome as well as an evaluative measure in clinical trials. Objectives : The objectives of this study were to translate SAQLI into the Malay language and to determine the feasibility, validity and reliability of the Malay version of SAQLI. Study design and methodology : This was a cross sectional study conducted at Sleep and General ORL-HNS Clinic, Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. Eighty two respondents were involved. The Malay translated SAQLI and a previously Malay translated and validated Short Form 36 (SF-36) were administered by interviewer. The translation used forward, backward and respondent testing and has been reviewed for face and content validity. The Malay translated SAQLI were administered again at two to four weeks interval. Analysis included the determination of the scaling assumptions, feasibility, reliability and validity. Results : All subjects completed the questionnaire successfully. The Malay version of SAQLI has no floor or ceiling effects. The four domains of the Malay SAQLI have means ranging from 3.59 to 4.82 and standard deviation, sd ranging from 0.846 to 0.945. The Cronbach’s alpha were very high >0.95 for all domains; domain daily functioning: 0.966, domain social interaction 0.981 and domain emotional functioning 0.971 suggested items redundancy. The standard of test-retest reliability was also fulfilled with intraclass correlation coefficients were excellent ranging from0.796 to 0.984. The Pearson item-scale correlation between item and its hypothesized scale was 0.4 or above, thus item-scale convergent and discriminant validity were satisfied. Factor analysis showed items in the three domains all loaded on the hypothesized scales. Known group validity showed no significant correlations between SAQLI and AHI (p>0.05). Criterion validity was confirmed by significant correlations with SF-36 subscale scores. Conclusion : The translation of the Malay version of SAQLI was acceptable. The feasibility is present and the scaling assumptions met. The internal consistency and intraclass correlation coefficients were excellent. The content validity has been established with evidence of acceptable construct and criterion validity. The Malay version of SAQLI should be used in the management and studies involving OSAS patients and a shorter version of SAQLI is recommended.